Mental aberrations and other demographic factors influencing homicide - Bhattacharya, Partha; Chakraborty, Prabir; Das, Somnath; Maiti, Rina; Sharma, Mukul (International Journal of Medical Research and Review, 2014)
Introduction: It has been a long search for the identification of the personality trends among the people committing homicides. The present work searches for the type of personality disorder among the homicide offenders and identify its demographic profiles in a cross-sectional study at a correctional home at Kolkata. Methods: Psychiatric examination reports and crime reports of the offenders were subjected to forensic examination. [n=69]. Results: Most of the offenders were found to be male, aged more than 30 years, less educated and economically backward. While delusional beliefs were found to be primary mental aberrations among the homicides. Conclusion: Homicide offenders do have a psychopathic trait and environmental influences also have an important role to play.